Respostas

2013-11-27T12:08:35-02:00
1/2 - 1/3 + 5/6 - 3/4 = 
mmc de (2, 3, 6 e 4)
2, 3, 6, 4|2
1, 3, 3, 2|2
1, 3, 3, 1|3
1, 1, 1 ,1 / mmc = 2x2x3 --> mmc = 12

(12:2.1)/12 - (12:3.1)/12 + (12:6.5)/12 - (12:4.3)/12 = 
6/12 - 4/12 + 10/12 - 9/12 = (6-4+10-9)/12 = 3/12 = 3:3/12:3 = 1/4
3 4 3
2013-11-27T12:21:47-02:00
1 - 1 + 5 - 3 =
2   3    6   4

mmc
2, 3, 4, 6 | 2
2, 3, 2, 3 | 2
1, 3, 1, 3 | 3
1, 1, 1, 1   /  2² x 3 = 12

6 - 4 + 10 - 9 =
        12
 3   ---> simplificada: 1
12                            4

Resposta:
1
4
4 4 4